2022
DOI: 10.1039/d2nj03584g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of MgAl-LDH@ZIF-8 composites by in situ growth method for highly efficient phosphate removal

Abstract: Removal of phosphate from wastewater by adsorption has become one of the effective ways to mitigate the negative effects of eutrophication in water bodies, and efficient adsorbent is the key....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…2d) shows five distinct peaks corresponding to lattice oxygen (M–O–M) (M = Mg or Al), low coordination oxygen, hydroxyl groups (M–OH), C–OH, and CO 3 2− , respectively. 36,37 Karst-LDH has a higher proportion of low coordination oxygen (27.74%) than that of G-LDH (19.64%) and Rock-LDH (24.06%), suggesting more storage and transfer of active oxides in Karst-LDH. 38 The Mg 1s spectrum (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…2d) shows five distinct peaks corresponding to lattice oxygen (M–O–M) (M = Mg or Al), low coordination oxygen, hydroxyl groups (M–OH), C–OH, and CO 3 2− , respectively. 36,37 Karst-LDH has a higher proportion of low coordination oxygen (27.74%) than that of G-LDH (19.64%) and Rock-LDH (24.06%), suggesting more storage and transfer of active oxides in Karst-LDH. 38 The Mg 1s spectrum (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…For the −OH absorption peak, the wavenumber varied from 3425 to 3375 cm –1 after adsorption, significantly shifting toward the lower wavenumbers, indicating enhanced hydrogen bonding. It is indicated that the phosphate exchanged ligands with the −OH group on ZIF-8-PhIm …”
Section: Resultsmentioning
confidence: 99%
“…It is indicated that the phosphate exchanged ligands with the −OH group on ZIF-8-PhIm. 51 In summary, the mechanism of phosphate adsorption can be summarized in two key interactions: (1) Zn−O−P bonding and (2) electrostatic attraction of the negative phosphate ion to the positive ZIF-8-PhIm surface. The increase in pore size and pore capacity of ZIF-8-PhIm increased hydrophilicity and exposed more active sites for adsorption (Figure 11).…”
Section: Isotherms and Thermodynamicsmentioning
confidence: 99%
“…NH 2 -MIL-101 has a higher adsorption capacity than MIL-101, which may result from the amine functional groups that can interact with phosphate ions, and the different mechanisms were discussed in Figure b. In a recent study by Dai et al, MgAl-LDH@ZIF-8 composites were prepared by in situ growth of zeolite imidazole framework-8 (ZIF-8) on MgAl-LDH for phosphate removal in wastewater . Compared with pure ZIF-8 and MgAl-LDH, the prepared LDH/MOF composite has a higher phosphate removal efficiency of up to 99%.…”
Section: Progress Of Ldhs In Phosphate Removal and Recyclingmentioning
confidence: 99%